2020
DOI: 10.1002/chem.202001902
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid and H‐Bond Activation in Boronic Acid Catalysis

Abstract: Boronic acid catalysis has emerged as am ild method for promoting aw ide variety of reactions. It has been proposed that the mode of catalysis involves Lewis acid or covalent activation of hydroxyl groupsb yb oron, but limited mechanistic evidencee xists. In this work, representative boronic acid catalyzedr eactions of alcohols and oximes have been reinvestigated. As eries of control experiments with boronic and Brønsted acids were interpreted along with correlations between their reactivity and their acidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 78 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…Indeed, we noticed that boronic acids were able to trigger a cyclopropane ring opening in HFIP, although no hydroxyl group was present (Scheme 8) (see part 5 for details). 21 Therefore, we reinvestigated a series of BAC reactions with alcohols and oximes. At the outset, we examined several boronic and Brønsted acids using the Gutmann-Beckett method, 22 which revealed that strong Brønsted acids are very likely to be produced by B1 and B3 in HFIP (Figure 2).…”
Section: Friedel-crafts Alkylationsmentioning
confidence: 99%
“…Indeed, we noticed that boronic acids were able to trigger a cyclopropane ring opening in HFIP, although no hydroxyl group was present (Scheme 8) (see part 5 for details). 21 Therefore, we reinvestigated a series of BAC reactions with alcohols and oximes. At the outset, we examined several boronic and Brønsted acids using the Gutmann-Beckett method, 22 which revealed that strong Brønsted acids are very likely to be produced by B1 and B3 in HFIP (Figure 2).…”
Section: Friedel-crafts Alkylationsmentioning
confidence: 99%
“…Increased understanding of the role of these solvents will facilitate the development of more industrially viable protocols. For example, recent work by Moran and co‐workers suggest the formation of supramolecular assemblies between BCF⋅H 2 O and nitro‐additives, [67] while many boronic acid catalysts are likely to form strong Brønsted acids in situ using the solvent [17] . These insights further highlight the importance of the solvent in such processes and will help in the design and study of future catalytic systems.…”
Section: Discussionmentioning
confidence: 93%
“…In most cases, these reactions work well with activated allylic alcohols or electron‐rich benzylic alcohols, but do not tolerate substrates bearing strongly electron‐withdrawing substituents. A recent study by Moran suggests that the mode of activation of alcohols using arylboronic acids is likely to be due to either Brønsted acid or H‐bond catalysis, rather than Lewis acid catalysis as initially postulated [17] . Building upon their seminal work in the area, [18] Hall and co‐workers discovered that a combination of 2,3,4,5‐tetrafluorophenylboronic acid 6 (10 mol %) and perfluoropinacol 7 (10 mol %) was effective for Friedel–Crafts alkylation reactions using a range of benzylic alcohols, including those bearing electron‐withdrawing substituents [19] .…”
Section: Dehydrative C−c Bond Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…In solution, pentafluoro­phenyl­boronic acid 1 and oxalic acid 2 are in dynamic equilibrium with hydrated boronate 39 , which is likely to act as a Brønsted acid to protonate the secondary benzylic alcohol. This is consistent with recent work by Moran and co-workers, who found that various arylboronic acid promoted alcohol activation processes are likely to proceed via either a Brønsted acid or H-bond activation mode, as opposed to Lewis acid or covalent catalysis . Dissociation of ion pair 40 forms benzylic carbocation 41 , which can undergo nucleophilic addition from the enol tautomer of either the 1,3-diketone derivatives or 1,3-ketoesters to form the C -alkylation products and release water as the only byproduct.…”
mentioning
confidence: 99%